2023
DOI: 10.1002/aic.18314
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous ozone and hydrogen peroxide electrosynthesis via defect modulation in Ni, Sb‐doped SnO2 electrocatalysts

Lei Ding,
Wenwen Li,
Mingzhe Xue
et al.

Abstract: Electrochemical synthesis of green oxidants O3 and H2O2 is valuable for applications, but challenges persist in enhancing the O3 and H2O2 generation activity and combined application. Herein, we modulate the surface Ni active sites and oxygen vacancy defects content in Ni‐Sb‐SnO2 electrocatalysts to enhance selectivity for electrochemical ozone generation (EOP) and two‐electron electrochemical oxygen reduction reactions (2e− ORR). The Ni active sites and oxygen vacancy defects enriched electrocatalysts resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Our group showed that increasing the thickness of NATO electrodes increased both reaction activity and selectivity, which cannot be explained without invoking transport of solution-phase intermediates . Work by Ding et al and Zhang et al revealed that NATO catalysts generate hydroxyl radicals ( • OH). , Lansing et al showed that quenching • OH had a minimal effect on EOP from NATO electrodes, while quenching hydroperoxyl radicals ( • OOH) significantly decreased it . These findings diverge from the conventional perspectives of both AEM and LOM, which typically assume the involvement of only surface-adsorbed intermediates.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Our group showed that increasing the thickness of NATO electrodes increased both reaction activity and selectivity, which cannot be explained without invoking transport of solution-phase intermediates . Work by Ding et al and Zhang et al revealed that NATO catalysts generate hydroxyl radicals ( • OH). , Lansing et al showed that quenching • OH had a minimal effect on EOP from NATO electrodes, while quenching hydroperoxyl radicals ( • OOH) significantly decreased it . These findings diverge from the conventional perspectives of both AEM and LOM, which typically assume the involvement of only surface-adsorbed intermediates.…”
Section: Introductionmentioning
confidence: 78%
“…Figure 5 A shows that both NATO (EOP active) and ATO (EOP inactive) generate • OH at 2.70 V, consistent with the literature. 7 , 43 , 44 , 77 • OH radicals were detected via their selective reaction with benzoic acid to generate hydroxybenzoic acids. Importantly, benzoic acid should be selective to • OH because the presence of the carboxylic group in benzoic acid deactivates the electrophilic substitution reaction by O 3 .…”
Section: Discussion and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these methods, six-electron electrochemical ozone production (EOP) holds significant potential. Ozone (O 3 ) is a potent oxidizer with a lower environmental impact than traditional disinfectants, and it can be generated on site through EOP. Furthermore, EOP produces hydrogen as a byproduct, potentially enhancing the cost-effectiveness of water treatment .25ex2ex 3 H 2 O O 3 + 6 H + + 6 e E = 1.51 V vs RHE .25ex2ex 2 H 2 O O 2 + 4 H + + 4 e E = 1.23 V vs RHE …”
mentioning
confidence: 99%
“…Ozone (O 3 ) is a potent oxidizer with a lower environmental impact than traditional disinfectants, and it can be generated on site through EOP. 2 5 Furthermore, EOP produces hydrogen as a byproduct, potentially enhancing the cost-effectiveness of water treatment. 6 …”
mentioning
confidence: 99%